Policy Gaps and Health Risks: Addressing Women’s Indoor Air Pollution Exposure in Pakistan - Habib, Nargis; Habib, Sehrish; Hassan, Mehreen; Shafi, Ahsan; Nawaz, Muhammad Haseeb (International Journal of Engineering and Management Sciences, 2026)
Indoor air pollution currently poses a significant challenge, adversely impacting both the physical and mental health of women. The substantial use of fossil fuels for domestic chores endangers women's health and exposes them to considerable risks. In this regard, this study elucidates the factors driving the use of fossil fuels in domestic kitchens in Pakistan. The association between primary indicators such as women's health, duration of women’s current pregnancy, and pregnancy status with household air pollution is analyzed. We use Ordinary Least Squares (OLS) regression in Stata, and the results indicate that the type of cooking fuel significantly affects women's health. Furthermore, indoor cooking also negatively influences the duration of pregnancy. Based on these results, the paper provides practical policy recommendations for governments and policymakers to mitigate health risks. This study is instrumental in analyzing the current state of household air pollution, offering a robust model for countries heavily reliant on fossil fuels, and examining the consequent health impacts on women.